THE ARTISTIC SKILL OF KAFKA AND THE SCENE OF THE UNFINISHED PROCESS - Abduramanova, Diana (Журнал иностранных языков и лингвистики, 2023)
In everything created by human hands, heart and affection, love and compassion, suffering and truth, justice and poverty live like twins. If the beautiful result of this suffering is art, then there will always be spiritual purification, healing after purification, perfection. More often than not, writers who desire a world they don't understand "find out too late what they've drawn." What they know is a drop in the ocean.